PENGARUH TPA TERHADAP PENINGKATAN PROGRAM TAHFIDZ QURAN DI SMP ISLAM TSAMROTUL HUDA SIDOHARJO GEDEG MOJOKERTO - Ali Muhsin (Universitas Islam Lamongan, 2017)
The Qur'an is very important to the life of all mankind and we must take into account it. On this stand, we could take into account the Qur'an by reading, understanding, and memorizing it. To be able to understand the content of the Qur'an, we must firstly be able to read it. That's why the Tsamrotul Huda Islamic Junior High School (SMP) includes the TPQ program and so-called Tahfidz Qur’an program into its education curriculum. This study is aimed at determining the influence of TPQ on the increase of Tahfidz Qur’an program in Tsamrotul Huda Islamic Junior High School Sidoharjo Gedeg Mojokerto especially the program in 2016/2017. This study used quantitative method. The researcher used interview, tests, documentation and observation to collect data. The result of this research is knowing a significant correlation between TPQ program and the increase of Tahfidz Qur’an program in Tsamrotul Huda Islamic Junior High School. This is proved through the value of ro (count) that is greater than the value of rt (table).Keywords: TPQ, Tahfidz Qur'an Program